2017
DOI: 10.1002/ijc.31011
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fecal microbial markers in colorectal cancer detection

Abstract: Colorectal cancer (CRC) is the second most common cause of cancer death in the western world. An effective screening program leading to early detection of disease would severely reduce the mortality of CRC. Alterations in the gut microbiota have been linked to CRC, but the potential of microbial markers for use in CRC screening has been largely unstudied. We used a nested case–control study of 238 study subjects to explore the use of microbial markers for clbA+ bacteria harboring the pks pathogenicity island, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(183 citation statements)
references
References 45 publications
4
163
1
Order By: Relevance
“…Our hypothetical distribution was the distribution of the necessary condition. Thus far, the data as published by Eklöf et al [35] do support our null hypothesis that an infection by Fusobacterium is a conditio sine qua non of colorectal carcinoma. In other words, without an infection by Fusobacterium no colorectal carcinoma.…”
Section: Proofsupporting
confidence: 80%
See 3 more Smart Citations
“…Our hypothetical distribution was the distribution of the necessary condition. Thus far, the data as published by Eklöf et al [35] do support our null hypothesis that an infection by Fusobacterium is a conditio sine qua non of colorectal carcinoma. In other words, without an infection by Fusobacterium no colorectal carcinoma.…”
Section: Proofsupporting
confidence: 80%
“…The studies of Fukugaiti et al [31], Vogtmann et al [32] (two sided), Li et al [33], Amitay et al [34], Eklöf et al [35], where able to provide evidence that Fusobacterium is a necessary condition, a conditio sine qua non, of colon cancer. Con-sistent with this finding, the current study using data published by Ahn et al [30], Vogtmann et al [32] documented a significant cause effect relationship between Fusobacterium and colon cancer while the studies of Li et al [33], Amitay et al [34], Eklöf et al [35] were able to provide evidence of a highly significant cause effect relationship between Fusobacterium and colon cancer. In particular, we need to bear in mind that Li et al [33] were able within certain limits to provide evidence that Fusobacterium nucleatum is a necessary and sufficient condition of human colorectal cancer.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A striking example is our recent identification of the link between Fusobacterium nucleatum and the chemoresistance to CRC . We and others also showed that gut microbiota alone could predict CRC well, highlighting a potential clinical application of gut microbiota as a noninvasive screen strategy for early detection of CRC in population . Despite the enormous efforts and substantial progress, only minor improvements have been achieved in the clinical outcome of patients with CRC.…”
Section: Introductionmentioning
confidence: 84%